Preserving the mind from the perspective of religious discourse and its role in building society (Journal of Human Sciences, 2021)
The aim of  the  present research is to study and preserve the  human mind  as a significant purpose of the Islamic law (shariah). The researcher   functionalized  a concept of religious discourse  as the privacy   of talking to others. Human mind is  a  most magnificent  bounty bestowed by- God to whom   be ascribed all perfection and majesty- upon   human beings. Much interest  inreligious discourse was given a primary concern with  the psycho-educational dimention, to control human behavior as well as guiding it to address the whole  nation to the Holly Quran and the  Sunnah of Mohammad(blessings and peace be upon him) that preserve human mind,  protecting it from the blights  that hinder its functions towards his Creator and the human society. This research has concluded a number of findings.  The most   important one  is moral educational guidance  and Islamic    education, as it required in  both    the Holly Quran and Sunnah of prophet Mohammad (peace be upon him) , which is the most significant  method that preserve  human mind The research  has also revealed   that human beings can protectthem selves through participating in buildingsociety by mind preservation.